2015
DOI: 10.1148/radiol.14132111
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Pleural Mesothelioma: Visual Assessment by Using Pleural Pointillism at Diffusion-weighted MR Imaging

Abstract: Visual assessment of pleural pointillism on high-b-value DW images is useful to differentiate MPD from benign alterations, performing substantially better than mediastinal pleural thickness and shrinking lung, and might obviate unnecessary invasive procedures for MPM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 22 publications
4
37
0
1
Order By: Relevance
“…As a result, optimal imaging conditions were only achieved in 108/315 (34%) of the patients studied. The development of objective imaging biomarkers of PM may therefore provide a better long-term method of reducing inter-observer disagreement in CT reporting, as has previously been demonstrated in breast cancer [11], [12] Novel objective imaging markers of PM are also under development including Pleural Pointillism [13] and Early Contrast Enhancement [14], both defined using MRI.…”
Section: Discussionmentioning
confidence: 98%
“…As a result, optimal imaging conditions were only achieved in 108/315 (34%) of the patients studied. The development of objective imaging biomarkers of PM may therefore provide a better long-term method of reducing inter-observer disagreement in CT reporting, as has previously been demonstrated in breast cancer [11], [12] Novel objective imaging markers of PM are also under development including Pleural Pointillism [13] and Early Contrast Enhancement [14], both defined using MRI.…”
Section: Discussionmentioning
confidence: 98%
“…More recent studies have highlighted potential utility for diffusion-weighted MR imaging (DWI-MRI) in differentiating pleural malignancy from benign pleural disease, with lower Apparent Diffusion Coefficient (ADC) values being demonstrated in pleural malignancy 31 32 . Coolen et al also performed DWI-MRI in a study of pleural malignancy and reported that inhomogeneous restriction in diffusion of the thickened pleura differentiates malignant from benign pleural disease with a sensitivity of 92.5% (95% CI 84% to 97%) and specificity of 79% (95% CI 62% to 89%) 33 . Gill et al demonstrated that patients with epithelioid MPM have a significantly higher ADC value than those with non-epithelioid MPM and an ADC threshold of 1.1 could differentiate epithelioid MPM from sarcomatoid MPM with a sensitivity of 60% and specificity of 94% (95% CIs not reported) 32 .…”
Section: Section 5: Imaging Modalities For Diagnosing and Stagingmentioning
confidence: 99%
“…The features of malignant pleuropathy have been well described in literature and can be summarized as: circumferential pleural thickening (pleural rind); thickened mediastinal pleura; nodular or lobular borders within the internal profile; irregular borders of the external profile (infiltration of the wall); mediastinal and pericardial infiltration, lymph nodes in extra pleural fat tissues (7)(8)(9)(10)(11)(12). Pleural effusion is an unspecific sign and pleural calcific or not calcific plaques are indicative of asbestos exposure but not of neoplastic pathology (8).…”
Section: Review Articlementioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is not routinely performed in the clinical practice for patients with MPM; there is some evidence in literature that MRI signal could be useful to differentiate malignant pleuropathy from benign pleural fibrous plaque (12,16). MRI is better than CT for detecting invasion of chest wall, mediastinal and nervous structures as brachial plexus, and peritoneum (15) and is generally reserved for those patients eligible for surgical treatment.…”
Section: Review Articlementioning
confidence: 99%